Efficient Catalytic Ozonation over Reduced Graphene Oxide for p-Hydroxylbenzoic Acid (PHBA) Destruction: Active Site and Mechanism. - Wang, Y.; Xie, Y.; Sun, H.; Xiao, J.; Cao, H.; Wang, Shaobin (American Chemical Society, 2016)
Nanocarbons have been demonstrated as promising environmentally benign catalysts for advanced oxidation processes (AOPs) upgrading metal-based materials. In this study, reduced graphene oxide (rGO) with a low level of structural defects was synthesized via a scalable method for catalytic ozonation of p-hydroxylbenzoic acid (PHBA). Metal-free rGO materials were found to exhibit a superior activity in activating ozone for catalytic oxidation of organic phenolics. The electron-rich carbonyl groups were identified as the active sites for the catalytic reaction. Electron spin resonance (ESR) and radical competition tests revealed that superoxide radical ((•)O2(-)) and singlet oxygen ((1)O2) were the reactive oxygen species (ROS) for PHBA degradation. The intermediates and the degradation pathways were illustrated from mass spectroscopy. It was interesting to observe that addition of NaCl could enhance both ozonation and catalytic ozonation efficiencies and make ·O2(-) as the dominant ROS. Stability of the catalysts was also evaluated by the successive tests. Loss of specific surface area and changes in the surface chemistry were suggested to be responsible for catalyst deactivation.